Implementation of Solar Power Plant as a Backup Power Source in Apartment Buildings - Muhammad Ryan Hafizan; Azriyenni Azhari Zakri; Dirman Hanafi; Umair Ali (International Journal of Electrical, Energy and Power System Engineering)
Indonesia has an average solar energy potential of 4.8 kWh/m²/day with a monthly variation of around 9%, providing opportunities for renewable energy utilization through Solar Power Plants to reduce dependence on fossil fuels and lower carbon emissions. This study is applied to The Lana Apartment, projected to have high electricity consumption. The main supply comes from PLN with a capacity of 2000 kVA, while backup power is provided by a generator with a capacity of 1250 kVA. To reduce reliance on the generator, this study aims to design and analyze Solar Power Plants as an environmentally friendly backup power system for the apartment. The Solar Power Plants design was created using HOMER software to model energy production potential, calculate power requirements, and evaluate system performance using the performance ratio. Simulation results show that the designed Solar Power Plants have a capacity of 2997.28 kWp, an inverter capacity of 3500 kW, and a battery capacity of 50160 Ah. This system can generate approximately 4,165,251.97 kWh per year with a performance ratio of 79.32%, indicating good operational efficiency in line with optimal Solar Power Plants standards. The implementation of these Solar Power Plants is expected to provide a more environmentally friendly backup power alternative and potentially reduce operational electricity costs in the apartment building.